Seasonal variability of water quality by physicochemical indexes and traceable metals in suburban area in Kikwit, Democratic Republic of the Congo - Alexis B. Nienie; Periyasamy Sivalingam; Amandine Laffite; Patience Ngelinkoto; Jean-Paul Otamonga; Alphonse Matand; Crispin K. Mulaji; Josué I. Mubedi; Pius T. Mpiana; John Poté (International Soil and Water Conservation Research, 2017)
Water resource contamination is still a major concern in several regions of developing countries especially in sub-Saharan countries in which polluted waters pose serious risks to human health and the environment. The seasonal variation of the physicochemical parameters including pH, temperature (T), electrical conductivity (EC), dissolved oxygen (O2), dissolved organic carbon (DOC), total organic carbon (TOC), and trace metals were assessed in water samples collected from wells (n=3) and two rivers which were the River Lukemi (RLK, n=3) and River Luini (RLN, n=2) located in the City of Kikwit (Province of Kwilu, Democratic Republic of the Congo). Samples were collected during the dry and wet seasons. The concentration of trace metals (Cr, Mn, Co, Ni, Cu, Zn, As, Mo, Ag, Cd, Sn, Sb, and Pb) in water was measured using Inductively Coupled Plasma Mass Spectrometry (ICP-MS), and soluble ions (Na+, K+, NH4+, SO42-, NO3-, and Cl-) analysis was performed using Ion Chromatography. The results indicate the seasonal difference in the physicochemical composition of water e.g., the pH was lower in the wet compared to the dry season. pH values during the wet season ranged from 4.12 to 5.60 in wells and from 5.55 to 6.31 in rivers while the dry season values ranged from 6.27 to 6.98 in wells and from 7.09 to 7.44 in rivers. The concentrations of soluble ions and other physicochemical parameters (O2, DOC and TOC) also varied with the seasons, being higher in the wet and lower in the dry season. With the exception of Mn, the average concentrations of other trace metals measured in water samples from wells and rivers met the World Health Organization (WHO) guidelines for drinking/domestic water quality. Mn concentration in water samples analysed ranged between 634 to 812 and 1352–1741 µg L−1 during the dry and wet seasons, respectively. These results imply that the high concentration of Mn in the water samples may be explained by the geological origin and result of natural weathering processes. In general, according to the parameters analysed, the water samples taken from the sites studied in both seasons appear to meet drinking water standards according to the WHO guidelines but with the two exceptions of the pH and Mn. This study is important for the present situation and can be applied in similar environmental compartments in the future to assess the availability of safe drinking water in developing countries.